2017
DOI: 10.22374/1875-6859.13.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occasional Alcohol Drinking on Semen Quality and Sperm Morphology among Young and Healthy Polish Men

Abstract: BackgroundEthanol (EtOH) is an agent that seems to exert an especially harmful effect on male fertility. The impact of high EtOH intake on fertility was demonstrated in numerous researches, with data suggesting that this effect may have been due to decreased semen quality; however, similar negative effects were not identified among occasional EtOH drinkers. There are currently no recommendations for alcohol consumption for men who plan to have a child other than avoiding high EtOH intake. Thus, studies on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 . Although there are fewer human studies, alcohol consumption of more than two standard drinks per day is linked to morphological changes in sperm 60 . One report of a very large study has found effects of heavy (more than five standard drinks per day) paternal but not maternal preconception drinking on offspring head circumference and risk of microcephaly 61 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 . Although there are fewer human studies, alcohol consumption of more than two standard drinks per day is linked to morphological changes in sperm 60 . One report of a very large study has found effects of heavy (more than five standard drinks per day) paternal but not maternal preconception drinking on offspring head circumference and risk of microcephaly 61 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Besides, Khat contains bioactive compounds such as alkaloids that influence fertility by decreasing semen quality. This is confirmed by Lwow et al (2017) who noted that a diet with a high concentration of alcohol seems to exert an especially harmful effect on male fertility due to its decreasing semen quality.…”
Section: Fertility Embryonic Mortality Hatchability and Chick Qualitymentioning
confidence: 63%
“…In our previous publications, we discussed in detail the overall quality of semen in the sample 13 and its associations with physical activity 12 and addiction. 14 The mean (± SD) concentration of 25(OH)D 3 in the volunteers was 13.7 ± 8.9 ng/mL, the mean semen volume 3.1 ± 1.5 mL, the mean sperm concentration 60 ± 44 × 10 6 /mL, the mean total sperm count 170 ± 137 × 10 6 /ejaculate, and the mean percent of normal forms 14.7 ± 6.5%.…”
Section: Resultsmentioning
confidence: 86%
“…The detailed characteristics of the participants, their flow through the study protocol, and the laboratory methodology were described in our previous publications. [12][13][14] In the included men, the mean age was 24.6 ± 3.6 years old, and the mean body mass index was 24.0 ± 2.8. Among the participants, 14% smoked cigarettes, and 92% drank alcohol.…”
Section: Methodsmentioning
confidence: 99%